1878 Cal Stat. 117 - (:unkn) unknown (My University, 1878)
An Act Amending Section Four Hundred and Fifteen of the Penal Code, in Relation to Crimes Against The Public Peace, ch. CCXCIX, § 1: Prohibited discharge of any gun or pistol in an unincorporated town. Violators fined not exceeding two hundred dollars, or imprisonment not exceeding ninety days, or both fine and imprisonment.
Keywords: DISCHARGE